Penerapan Metode Simpleks Berbasis Teknologi Informasi untuk Optimalisasi Keuntungan Kios di Pasar Modern - Matheus Supriyanto Rumetna; Tirsa Ninia Lina; Rafael Sahetapy; Restu Saharun; Oktopianus Langgi (Universitas Putera Batam, 2025)
The Rufei modern market in Sorong City was built to accommodate street vendors but still faces challenges such as low customer traffic and inadequate infrastructure. One affected trader is Kios Rizki, which struggles to maximize profits. To address this issue, the Simplex method is applied as a linear programming approach to find the optimal solution for profit maximization. This method enables iterative calculations to determine the best combination of decision variables. Additionally, POM-QM for Windows, a technology-based software, is used to enhance calculation accuracy and efficiency. The integration of quantitative methods with computational tools demonstrates how technology improves business decision-making. The results of manual calculations using the Simplex method and POM-QM for Windows show that Kios Rizki’s optimal profit is Rp 1,000,000 (one million rupiahs). Thus, implementing the Simplex method with information technology provides a strategic solution for increasing profitability in modern markets and highlights the role of technology in optimizing small businesses.